Answer
$x^{2}+12x$
Work Step by Step
Subtract the polynomials inside the brackets
$ \begin{array}{lllll}
& 4x^{2} & +7x & -5 & \\
-( & 2x^{2} & -10x & +3 & )\\
\hline & & & & \\
= & (4-2)x^{2} & +(7+10)x & +(-5-3) & \\
& & & & \\
= & 2x^{2} & +17x & -8 & \\
& & & & \\
& & & &
\end{array} $
From this difference, subtract the third polynomial.
$ \begin{array}{lllll}
& 2x^{2} & +17x & -8 & \\
-( & x^{2} & +5x & -8 & )\\
\hline & & & & \\
= & (2-1)x^{2} & +(17-5)x & +(-8+8) & \\
& & & & \\
= & x^{2} & +12x & +0 & \\
& & & & \\
& & & &
\end{array}$
= $x^{2}+12x$